Modeling of sediment discharge from Alaminos and Bani watersheds, Pangasinan province, the Philippines - Ratino Sith (College of Enginnering, University of the Philippines Diliman, 2013)
Increased sediment discharge from watershed adversely impacts the coastal marine environment, thus, the need to characterize the process in order to formulate potential effective mitigation measures. This study aims to characterize sediment discharge from Alaminos and Bani watersheds, which are located in the Province Pangasinan in the Northern Philippines. The Watershed Model System (WMS) and Geographical Information System (GIS) were used for data input, and output visualization. However, GSSHA model and ENVI were used to simulate runoff, river stage, sediment discharge and to map land cover respectively. The hydrological and hydro-meteorological data were collated to simulate the long term hydrologic modeling and sediment discharge modeling. Other input parameters such as roughness coefficient, hydraulic conductivity were derived from the relevant literature. For Alaminos Watershed, comparing the observed and simulated water and sediment discharge, the simulation were acceptably carried out. The efficiency performance indicators were found to be (ENS = 0.65, R2 = 0.67, PBIAS-21.51) for flow and (ENS=0.68, R2> 0.74) for sediment discharge. Over the entire watershed, it has been found that the high erosion area was located in the upper part of the watershed which is dominantly bare soil and steep slopes, while in the lower flat areas, there is no significant Occurrence of high erosion. For Bani watershed, water level and sediment discharge model were success fully calibrated with the efliciency performance indicators (ENS = 0.52 and R2 = 0.67, PBIAS=0.95) and (ENS = 0.85 and R2 = 0.91) respectively. The high erosion area is located in the Northern part where the region of rice field with high slope S. Land use and climate change scenarios were modeled in the period covering11- 25 June 2012, and 16-25 September 2011 for Alaminos and Bani watershed respectively. For both watersheds, Among the nine developed land use change scenarios, current base with soil conservation and upper buffer zone scenarios have most potentially decreased the sediment volume, and followed by 30% deforestation, 30% deforestation conversion to cropland, and 30% current base without soil conservation scenarios. For climate change, the simulation results indicated that the change of sediment volume has a trend of increase with the rainfall. In Alaminos watershed, AIB (2050) has potentially increased 250.99% of sediment volume as a result of 36.1% increase of rainfall, while A2 (2050) has also potentially decreased only 6.65% of sediment volume as result of 2.3% increase of rainfall. 1n Bani watershed, with 17.1% decrease in rainfall, the sediment volume has been decreased 93.03% while AlB (2020) has increased 73.20% of sediment volume as a result of 9.8% increase in rainfall. In conclusion, the calibrated GSSHA model is capable enough to simulate water and sediment discharge in the agricultural watersheds of Alaminos and Bani. Moreover, it can be used to simulate the sediment discharge with different scenarios such land cover change, and climate change.